Cryopreservation and fertility of ejaculated and epididymal stallion sperm - Monteiro, G. A. [UNESP]; Papa, Frederico Ozanam [UNESP]; Zahn, F. S. [UNESP]; Dell'aqua Junior, José Antônio [UNESP]; Melo, C. M. [UNESP]; Maziero, R. R. D. [UNESP]; Avanzi, B. R. [UNESP]; Alvarenga, Marco Antonio [UNESP]; Guasti, P. N. [UNESP] (Elsevier B.V., 2011)
The cryopreservation of epididymal sperm is important to preserve genetic material from valuable deceased males. This study evaluated the viability of sperm samples from eight stallions under three conditions: (1) collected using an artificial vagina (EJ-0 h), (2) recovered from the epididymal cauda immediately after orchiectomy (EP-0 h), and (3) recovered from the epididymal cauda after 24 h of storage at 5 degrees C (EP-24 h). To obtain EJ-0 h sperm, two ejaculates were collected from each stallion. After 1 week, the stallions were submitted to bilateral orchiectomy, and one of the removed epididymides was flushed to obtain EP-0 h sperm. The contralateral epididymis was stored at 5 degrees C for 24 h before being flushed to obtain EP-24 h sperm. The sperm samples were analyzed at three different times: immediately after sperm recovery, after dilution in the freezing extender, and post-thawing. A fertility trial was performed using 39 estrous cycles. After ovulation induction with 1 mg of deslorelin acetate (i.m.), mares were inseminated with 800 x 10(6) sperm. The total number of sperm recovered was 7.8 +/- 4.7 x 10(9) for EJ-0 h sperm, 12.9 +/- 9.2 x 10(9) for EP-0 h sperm and 12.0 +/- 8.0 x 10(9) for EP-24 h sperm. The sperm motility, evaluated by total motility, progressive motility and the percentage of rapid cells, was similar among the samples before and after freezing (P > 0.05). However, the plasma membrane integrity was different between EJ-0 h and EP-0 h pre-freezing and between EJ-0 h and EP-24 h post-thawing (P < 0.05). The conception rates were similar between groups inseminated with sperm recovered from the epididymal cauda immediately after orchiectomy (EP-0 h), after 24 h of storage at 5 degrees C of the epididymal cauda (EP-24 h) and with ejaculated sperm (EJ-0 h) (P > 0.05). In conclusion, the viability and fertility of cauda epididymal sperm are similar to those of ejaculated sperm. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Pregnancy rate; Epididymal spermatozoa; Stallion; Cryopreservation; Sperm viability